(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2024)
According to BKKBN, active family planning among PUS in 2019 was 62.5%, a decrease from the previous year, namely 63.27%. Meanwhile, the RPJMN target to be achieved in 2019 is 66%. The 2017 IDHS results also show a higher figure for active family planning, namely 63.6%. The highest active family planning was in Bengkulu, namely 71.4% and the lowest was in West Papua at 25.4%. This research is descriptive with a quantitative design using secondary data, namely the 2019 SKAP Data for Riau Province. Based on the 2019 SKAP data, it can be concluded that the majority of acceptors are aged 35-39 years, amounting to 268 (18%), acceptors have a high school education, namely 487 (39%), the acceptor’s occupation is non-working/IRT, namely 770 (61.7%), the upper wealth index is 484 (38.8), the place of residence of the acceptors is in rural areas 735(59%), 557 (55.9%) of the WUS acceptors who have ≥3 ideal children, do not know any modern contraceptive methods/methods is 144 (11.5%), EFA acceptors do not know any modern family planning tools/methods, namely 6 (0.6%), EFA acceptors obtain family planning information from the mass media 93.2%, EFA acceptors obtain family planning information from the mass media namely television 91.1%, officers who provide family planning information are midwives/nurses namely 725 (77.5%), EFA acceptors get information about family planning through institutions are community organizations 64.1%, WUS acceptors use 3 month injectable contraceptives namely 170 (13, 6%) and EFA acceptors use injectable contraceptives, namely 87 (17%). The majority of acceptors’ ages ranged from 35–39 years, totaling 268 (18%).